Vascular of the Heart of Rats Under the Influence of Pesticides - Akhmedova S. M; Abdikadirov Sh. I; Sagdullaeva M.K (Genius Journals, 2023)
The analysis of morphological and morphometric changes under the influence of pesticides on off spring of rats in the early postnatal ontogenesis passed through the mother's milk was made. Under the influence of pesticides, wall thickness of atrium and ventricles of all ages is reduced as compared with the control group. There is a reactive change in the vessels in the form of expansion and plethora, development of perivascular edema and diapedetic hemorrhage. In our opinion, this leads to disruption of the functional activity of the myocardium, eventually to the emergence of degenerative disorders in many organs and systems.
Keywords: rat heart; postnatal ontogenesis; pesticides